Am I Information Literate? and How Library Support My Information Needs? - Endang Ernawati (Bina Nusantara University, 2010)
Article clarifies information literacy (IL) implementation that is recognizing information needs, finding information, valuing, selecting information, creating new information and presenting it to get some inputs, applied in Cornel University, Dayton University, North Sumatera University, Duta Wacana University, and Bina Nusantara University. Data were collected by library research. It can be concluded that IL implementation in some mentioned universities have met the IL standards, IL is needed to develop students’ knowledge, skills, and performance, some IL have applied in the formal teaching activity, so that it needs to be researched so that all parties are satisfied and the goal of study can be achieved.